2021
DOI: 10.2147/ijgm.s300270
|View full text |Cite
|
Sign up to set email alerts
|

Role of Acupuncture in the Treatment of COPD: An Overview of Systematic Reviews

Abstract: Background Since consistent evidence on the effectiveness of acupuncture in the treatment of chronic obstructive pulmonary disease (COPD) is not available, this overview aims to summarize and critically evaluate the methodological and evidence quality of systematic reviews (SRs) on this topic. Methods Eight electronic databases were searched to identify relevant SRs of the use of acupuncture in the treatment of COPD from inception to January 2021. Two researchers indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…In a previous overview 28 closely related to this topic, acupuncture was investigated as either a primary or adjuvant treatment for COPD, the findings were similar to ours. This earlier overview identified nine SRs on acupuncture and demonstrated the therapeutic effects of acupuncture on 6MWD, SGRQ, FEV1%, and FEV1/FVC.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a previous overview 28 closely related to this topic, acupuncture was investigated as either a primary or adjuvant treatment for COPD, the findings were similar to ours. This earlier overview identified nine SRs on acupuncture and demonstrated the therapeutic effects of acupuncture on 6MWD, SGRQ, FEV1%, and FEV1/FVC.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, an overview was conducted to evaluate the role of acupuncture in the management of COPD. 28 However, the review did not include non-invasive acupuncture methods such as moxibustion and transcutaneous electrical acupoint stimulation.…”
Section: Introductionmentioning
confidence: 99%
“… 25 The results of this review are consistent with those of reviews in other areas (eg depression), 26 where methodological quality and strength of evidence were low or very low. Furthermore, Chun 27 reached the same conclusion in their study on the methodological quality and strength of evidence of reviews on acupuncture for COPD. Medical research suggests that there may be substantial methodological problems with acupuncture in the treatment of disease.…”
Section: Discussionmentioning
confidence: 55%
“… 53 Additionally, Chun et al assessed the methodological quality and strength of evidence of SRs/MAs regarding acupuncture in the treatment of COPD, and made the same conclusion. 55 The findings suggest that there may be serious methodological problems in SRs/MAs on the use of acupuncture in the treatment of diseases. Therefore, it must be acknowledged that double-blinding of acupuncture trials is not feasible, and sham controls are relevant only for efficacy studies, but not for studies testing the effectiveness relative to non-treatment or to another control intervention that can be easily distinguishable from acupuncture.…”
Section: Discussionmentioning
confidence: 98%
“…52 The results of this review were consistent with those from other fields (like chronic obstructive pulmonary disease (COPD), depression and hypertension). [53][54][55] For example, Zhao et al summarized the evidence of SRs/MAs about the application of acupuncture in hypertension. They concluded that the methodological quality and quality of evidence were unsatisfactory.…”
Section: Risk Of Bias In the Reviewmentioning
confidence: 99%